2015
DOI: 10.1016/j.ajo.2015.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Increased Fundus Autofluorescence and Progression of Geographic Atrophy Secondary to Age-Related Macular Degeneration: The GAIN Study

Abstract: FAF patterns, baseline area of atrophy, and time of follow-up were associated with GA progression. However, FAF patterns seem to be a consequence (not a cause) of enlarging atrophy and their effect on GA progression seems mostly driven by baseline area of atrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 32 publications
2
50
2
Order By: Relevance
“…In RPE flat mounts of AMD eyes, cells are seen to redistribute, aggregate, and overall lose autofluorescent granules in concert with cytoskeletal stress, as they degenerate. 9 Topographically precise longitudinal imaging in GA patients has shown that hyperAF indicates disease activity but does not predict atrophy on either a fine-grain 24 or population 95 basis. In AMD patients imaged with quantitative AF, which standardizes across populations via a fluorescent reference material in the light path, 96 FAF intensities decrease rather than increase.…”
Section: Discussionmentioning
confidence: 99%
“…In RPE flat mounts of AMD eyes, cells are seen to redistribute, aggregate, and overall lose autofluorescent granules in concert with cytoskeletal stress, as they degenerate. 9 Topographically precise longitudinal imaging in GA patients has shown that hyperAF indicates disease activity but does not predict atrophy on either a fine-grain 24 or population 95 basis. In AMD patients imaged with quantitative AF, which standardizes across populations via a fluorescent reference material in the light path, 96 FAF intensities decrease rather than increase.…”
Section: Discussionmentioning
confidence: 99%
“…An abnormal accumulation of lipofuscin is a major risk factor implicated in different forms of macular degeneration (Delori et al, 1995a; Marmorstein et al, 2002; Gerth et al, 2007; Biarnes et al, 2015), and also the most notable and consistent pathological finding in BEST1 -linked maculopathies, serving as an indirect biomarker of metabolic activity between the photoreceptor outer segment (POS) turnover and RPE phagocytosis (Bakall et al, 2007; Piñeiro-Gallego et al, 2011; Lei et al, 2013; Singh et al, 2013a). Recent advances with noninvasive retinal imaging modalities have enabled detailed mapping and quantification of fundus autofluorescence (FAF) in vivo , and its correlation with increased levels of lipofuscin components in the aged and diseased retinae (Delori et al, 1995a, 1995b; Brunk and Terman, 2002; Boon et al, 2008; Duncker et al, 2014); however, the polymorphous nature of lipofuscin material and consequences of its buildup in the retina are still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…2, 1820 The autofluorescent intracellular organelles containing these sources, lipofuscin (L), have further been implicated beyond biomarker status as an agent of AMD and Stargardt disease, and yet strong clinical evidence refutes this hypothesis. 18, 21, 22 _ENREF_19_ENREF_16 Clearly, the chemical composition of L is important to understanding human retinal disease.…”
Section: Introductionmentioning
confidence: 99%